Peculiarities of impairments of absorptive-excretory and glycogen synthesis functions of the liver in the presence of acute blood loss complicated by limb ischemia-reperfusion and their correction by carbacetam - Horban, I. I.; Hudyma, A. A.; Maksymiv, R. V.; Dzhavadova, N. A. (Journal of Education, Health and Sport, 2020)
Introduction. Under conditions of massive bleeding from the extremities, both in combat and in peacetime, the only means for salvation is applying tourniquet, which completely stops the arterial blood flow. It is believed that the maximum safe time for bleeding of the limb due to the use of the tourniquet is up to two hours. The systemic effect of acute blood loss complicated by ischemia-reperfusion of the limb on the liver, which is the main organ of detoxification of the body, remains almost unexplored. Objective of research: to determine the effect of acute blood loss complicated by two-hour limb ischemia and its reperfusion on the absorption-excretory and glycogen-synthesizing function of the liver. Materials of the research and their discussion. The experiments were performed on 108 nonlinear male rats weighing 200-220 g. All animals were divided into four groups: control and three experimental. All interventions were performed under thiopental-sodium anesthesia. In the first experimental group, the animals were simulated ischemia-reperfusion of the limb by applying a strip of elastic harness "SWAT-T" (USA)10 mm wide for 120 minutes proximal to the left paw. In the second experimental group, acute blood loss (20% of the circulating blood volume) was simulated by cutting the femoral vein. In the third experimental group, these injuries were combined. In the control group, the animals were anesthetized, and then taken for research after 1 hour. After 2 and 3 hours, as well as after 1, 7 and 14 days in experimental animals were determined by the absorption-excretory and glycogen-synthesizing functions of the liver. Result of the research and their discussion. It was found that the simulation of two-hour limb ischemia after 3 h and 1 day of reperfusion is accompanied by a significant decrease in hepatic excretory function, accompanied by a slowing of bile bromosulfalein excretion and its normalization starting from 7 days of the experiment. Under conditions of acute blood loss, the disorders deepen at all times of observation. Complications of acute blood loss by ischemia-reperfusion of the limb, contributes to a greater slowing of the absorption and excretory function of the liver compared to the simulation of only acute blood loss. The result was statistically significant after 7 and 14 days of the experiment. With regard to the content of glycogen in the liver, it was found that the simulation of only ischemia-reperfusion of the limb was accompanied by a significant decrease in the content of glycogen in the liver after 3 h of the experiment. Under conditions of acute blood loss, the rate was lower than the control level for seven days of the experiment. Additional ischemia-reperfusion of the limb on the background of acute blood loss caused a more pronounced decrease in glycogen content in the liver after 1 and 7 days of the experiment, which did not return to normal by 14 days of the experiment. The use of carbacetam showed that compared with animals without correction of the drug for 14 days significantly accelerated the purification of blood from bromosulfalein and normalized glycogen content. Thus, carbacetam is a promising means of correcting the functional state of the liver in conditions of acute blood loss complicated by ischemia-reperfusion of the limb, which requires further preclinical study. Conclusions. Complications of acute blood loss by two-hour limb ischemia in the reperfusion period lead to liver dysfunction, accompanied by a greater slowing of liver blood clearance from bromosulfalein compared to the model of isolated blood loss after 7 and 14 days of the experiment and a greater decrease in glycogen in the liver. The use of carbacetam for 14 days in the reperfusion period in animals with acute blood loss complicated by limb ischemia-reperfusion, compared with animals without correction, significantly accelerates hepatic clearance of bromosulfalein and normalizes glycogen content in the liver which indicates the prospects of carbacetam as a means of systemic correction in the simulated pathology. It could be the theoretical basis for its use in the clinic.